TEOLOGI LESA: STUDI TEOLOGI KONTEKSTUAL BUDAYA HIDUP ORANG WAIMAHU - Maria Christina Tetelepta; M M Hendriks; John Chr Ruhulessin (Program Pascasarjana UKIM, 2019)
Each society has its own traditional forms which passed down orally. These traditions demonstrate and explain the identity and characteristics of the community, which is closely connected to the world and the context in where they are located. The aim of this article is to discover values of Lesa. Lesa is one of the ancestral tradition of the Moluccans who usually live in groups, eat and live together. Contextual theology approach (practical mode) is developed in order to explore and examine life-lesa of Waimahu people. For Waimau people, lesa is a place in where all family members sit around to have meal together and a right time for parents to talk to children. Then, lesa is applied also to reconciliation. Shortly, Lesa means to gather a family together: sit together, have meal together, give thank to the Lord together, and enjoy reconciliation with God and neighbor. As cultural heritage, lesa must be transmitted to the new generation.